2009
DOI: 10.1063/1.3238549
|View full text |Cite
|
Sign up to set email alerts
|

Flow alignment phenomena in liquid crystals studied by molecular dynamics simulation

Abstract: The flow alignment of a nematic liquid crystal has been studied as a function of temperature, beginning at high temperature in the nematic phase and down to the nematic-smectic A phase transition. The alignment angle is obtained by estimating the twist viscosities by nonequilibrium molecular dynamics (NEMD) methods. These estimates are cross-checked by evaluating the corresponding equilibrium fluctuation relations. As a further comparison, shear flow simulations are carried out by application of the SLLOD equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Indeed, numerous equilibrium and nonequilibrium MD simulation studies of flow phenomena in bulk LC systems have been performed [19][20][21][22][23][24]. However, simulations of confined LC molecules subject to shear are less common: Simplified models of the Gay-Berne type have been considered [25,26], but, in general, to our knowledge, extensive numerical studies of LC lubricants have not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, numerous equilibrium and nonequilibrium MD simulation studies of flow phenomena in bulk LC systems have been performed [19][20][21][22][23][24]. However, simulations of confined LC molecules subject to shear are less common: Simplified models of the Gay-Berne type have been considered [25,26], but, in general, to our knowledge, extensive numerical studies of LC lubricants have not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that the stationary alignment observed for simple one component systems may be replaced by a so called tumbling behavior for more complex materials, e.g. nematic liquid crystals with pre-transitional smectic fluctuations [10,[31][32][33], polymeric liquid crystals [34][35][36][37] as well as dilute suspensions where individual particles rotate in shear flows (Jeffery orbits, [38]). For the limiting case of very dense suspensions direct interparticle forces dominate, leading to stationary flow alignment, analogously to what is expected for simple one component systems.…”
mentioning
confidence: 99%
“…This means that there is no orientation angle where the antisymmetric pressure is zero, so that no steady state is attained. Then the l i q u i dc r y s t a li ss a i dt ob ef l o wu n s t a b l ea n dt h ed i r e c t o rw i l lr o t a t ef o r e v e r [3, 4, 23,24].…”
Section: Shear Flow Of Nematic Liquid Crystalsmentioning
confidence: 99%